ANALISIS FAKTOR-FAKTOR KESULITAN MEMBACA MENULIS DAN BERHITUNG SISWA KELAS 1 SD - Mardika, Tiwi (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2019)
The research was aimed at knowing what factors affected the difficulty in reading, writing, and computing in first-grade elementary school. This used descriptive research. The subject of this research were 39 students of grade 1 at SD Negeri 1 Pancurendang. The data were collected through observation, interview, and documentation. Based on the result of the research, most of the students were able to read, write and compute well, but only two were not. The difficulties in reading, writing, and computing were affected by several factors such as the family environment factor, the parent’s attention, guidance and supervision which were very, important and influencing the student’s interest and motivation as well as the student’s environment in the learning process. To overcome the difficulties in reading, writing, and computing, the teacher and parents gave attention, training, and guidance so that the learning process could run well.